2022
DOI: 10.3390/ph15070830
|View full text |Cite
|
Sign up to set email alerts
|

Pentagalloyl Glucose and Cisplatin Combination Treatment Exhibits a Synergistic Anticancer Effect in 2D and 3D Models of Head and Neck Carcinoma

Abstract: Although cisplatin is a first-line chemotherapy drug for head and neck squamous cell carcinoma (HNSCC), its therapeutic efficacy is limited owing to serious side effects and acquired drug resistance. This study determined whether combining pentagalloyl glucose (PGG) and cisplatin enhanced their anti-tumor activities on HNSCC cell lines. We investigated the anticancer effect of PGG combined with cisplatin in 2D and 3D multicellular spheroid cell culture. The results revealed that PGG combined with cisplatin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…One approach that has attracted significant attention involves combining phytochemicals with low toxic profiles with conventional chemotherapeutic drugs. This combination therapy has shown the potential to induce synergistic effects, inhibit side effects, and overcome drug resistance [ 10 , 24 , 28 ]. In the present study, we demonstrated the ability of a phytochemical called PGG (previously isolated and purified from Bouea macrophylla seeds by our group) [ 23 ] to modulate the multidrug resistance protein P-gp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach that has attracted significant attention involves combining phytochemicals with low toxic profiles with conventional chemotherapeutic drugs. This combination therapy has shown the potential to induce synergistic effects, inhibit side effects, and overcome drug resistance [ 10 , 24 , 28 ]. In the present study, we demonstrated the ability of a phytochemical called PGG (previously isolated and purified from Bouea macrophylla seeds by our group) [ 23 ] to modulate the multidrug resistance protein P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that PGG exerts its anti-cancer effect through its anti-proliferative, pro-apoptotic, and anti-metastatic effects against various cancer cells, such as breast, lung, colon, and prostate cancers [ 18 , 19 , 20 , 21 ]. Moreover, PGG has been found to sensitize cancer cells to different anti-cancer agents and radiotherapy, rendering them more susceptible to treatment [ 22 , 23 , 24 ]. Notably, one intriguing mechanism by which PGG demonstrates its anti-cancer properties is by downregulating the expression of MDR1.…”
Section: Introductionmentioning
confidence: 99%
“…The results of in silico molecular docking and western blotting suggested that PGG treatment reduced the expression of phosphorylated STAT3. The computational approaches indicated that PGG was an inhibitor of STAT3 [ 128 ]. In addition, PGG suppressed the STAT3 expression in HeLa cervical cancer cells, thereby decreasing cell viability and increasing the cleaved PARP concentrations [ 63 ].…”
Section: Molecular Mechanisms Of Anticancer Effects Of Pggmentioning
confidence: 99%
“…The combination treatment was more effective in decreasing the size of 3D multicellular spheroid than monotherapies. Taken together, the combination therapy of PGG and cisplatin synergistically decreased cancer cell viability and induced apoptosis in 2D and 3D models [ 128 ].…”
Section: Synergistic Effect Of Pgg On Cancer Chemotherapy and Radioth...mentioning
confidence: 99%